Training, match and non-rugby activities in elite male youth rugby union players in England - Hendricks, S.; Till, K.; Weaving, D.; Powell, A.; Kemp, S.; Stokes, K.; Jones, B. (International Journal of Sports Science & Coaching, 2019)
Rugby union is a late specialisation sport. As a consequence, youth players may still be engaged in other activities and sports throughout the year as they transition to rugby specialisation. Limited research exists quantifying rugby union training and matches as well as engagement in other activities and sports. Therefore, the aim of this study was to quantify and compare rugby union training, matches and other activities of elite youth U15 and U16 rugby union players at different stages of the season. Four-hundred and ninety-two youth (Under-15 and 16-year-old) rugby union players self-reported the frequency, intensity and duration of their participation in rugby union matches, rugby union training, gym, physical education and other sports during three different stages - September to December (Sept-Dec), January to April (Jan-Apr), May to August (May-Aug) - of the year. When all activities were combined, the frequency and volume of rugby matches and training was the greatest during the Sept-Dec stage. The frequency and volume of participating in other sports increased in the May-Aug stage of the season. Gym training frequency, intensity, and duration were stable across the year for both U15 and U16 players. Coaches and practitioners working with elite youth rugby union players should be aware that players are still participating in other activities outside of rugby training and competition. Coaches and practitioners should put structures in place to plan and monitor players' activities in order to optimise the positive outcomes of specialisation (e.g., expertise) while reducing the potential negative outcomes (e.g., injury, burnout).